STRATIGRAPHIC TRAP ANALYSIS OF EARLY PLIOCENE ÃâÃâKB45ÃâÃâ SANDSTONE RESERVOIR, KAMPUNG BARU FORMATION, BONTANG PSC, NORTHERN KUTAI BASIN - PRASETYA, ANOM
Nowadays exploration focused in offshore Kutai Basin mainly taking place in offshore Central Kalimantan and offshore Southern Mahakam Delta, its normal strategy because siliciclastic sediments influx are filling this area in every period of Neogene age. Following successful exploration wells drilled by Salamander Energy in offshore Bontang, it open the exploration concept of deepwater play in this area, especially in the Early Pliocene lowstand sequence. Angkeu-1 drilled by Salamander to tested the structural trap of Angkeu-1 normal fault, and successfully found gas column in the Early Pliocene ‘KB45’ sandstone reservoir. Following the successful of Angkeu-1, in 2013 Salamander drilled the SK-1 to tested stratigraphic trap of same Early Pliocene ‘KB45’ sandstone reservoir and it successfully found oil and gas, but unfortunately Betty-1 which was drilled after SK-1 in the crest of Betty High did not found the early Pliocene ‘KB45’ sandstone reservoir. This results indicates the sedimentation of ‘KB45’ reservoir was not deposited trough Betty High. Because of the limitation of wells data, seismic sequence stratigraphy approach offers complete method to predict and reconstruct the stratigraphic trap and the hydrocarbon trapping mechanism. Seismic facies showing sigmoid oblique in lowstand sequence in the western part of the Betty High and to the East we will found seismic facies of the channel and fan system. Seismic sequence stratigraphy analysis provides four main sequence markers within NN12 – NN14 of Late Miocene – Early Pliocene age, which are SB1, MFS, SB2, and SB3. From four main sequence marker can be divided to three system tract sequence, which are Transgressive system tract (TST), Highstand System Tract (HST), and Lowstand System Tract (LST). Potential stratigraphic trap in LST sequence lies in the western flank of Betty High, because Angkeu normal fault creates the accommodation space for lowstand sediments. Lowstand sediments loading in lowstand sequence triggered the movement of coupled syn-sedimentary normal-toe-thrust faults systems of Angkeu normal faults and Betty toe-thrust. Angkeu normal fault also have a role as migration pathway for hydrocarbon trapping mechanism in Angkeu-1 and SK-1 wells.